Pengaruh Leverage, Profitability, Ukuran Perusahaan Dan Proporsi Kepemilikan Institusional Terhadap Tax Planning - Ika Nurjanah; Jeni Susyanti; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
Abstract             Thus study examines the impact of leverage, profitability, size, the proportion of institusional on tax planning. The population in this study is an manufacturing ompany listed on the Indonesia Stock Exchange (IDX) period of 2015-2017. The sample in this study is determined by purposive sampling with 10 companies. The method of analysis is using panel regression model. The result showed that leverage not be significant of tax planning (0.634), profitability not be significant of tax planning (0.888),size not be significant of tax planning (0.557),the proportion of institusional not be significant of tax planning (0.392).Keywords : leverage, profitability, size, the proportion of institusional, tax planning.